Cross-tool communication from protocol authoring to eligibility determination - Gennari, J H (Proceedings. AMIA Symposium, 2001)
To be effective, informatics tools for clinical trial protocols must inter-operate and share knowledge. We demonstrate a simple XML-based communication of eligibility criteria information between two independently-developed informatics tools. Using a shared DTD model of criteria, an authoring tool (developed within the Protégé environment) can send a list of eligibility criteria to a commercial system for automatic eligibility determination (the "iKnowChart" system by iKnowMed). The criteria model, developed as a Protégé ontology, includes both the terminology and the logic needed to compute eligibility for a given patient. As a demonstration of cross-tool communication, we have encoded criteria from an active clinical trial protocol (E1199), and shown how use of the authoring tool can effectively update the eligibility knowledge and the behavior of the commercial iKnowChart system. As part of the cross-tool knowledge sharing, we use Common Data Elements, an oncology terminology developed by the National Cancer Institute